Dietary Additive Combination for Dairy Calves After Weaning Has a Modulating Effect on the Profile of Short-Chain Fatty Acids in the Rumen and Fecal Microbiota - Dos Santos T.L.* (2024)
© 2024 by the authors.Background: This study aimed to verify whether adding a combination of additives (blend) to the diet of dairy calves after weaning can improve animal performance and health and influence the profile of ruminal short-chain fatty acids and intestinal microbiota. Methods: We used 35 Holstein calves, males, with an average age of 70 days and an average body weight of 68 kg. The treatments used were negative control (T-0: without additive), positive control (T-Control: flavomycin + monensin), T-500 (500 g blend/ton), T-1000 (1000 g blend/ton), and T-1500 (1500 g blend/ton). The additives were classified as zootechnical (probiotics, prebiotics, and essential oils of cinnamon and oregano) and nutritional additive (minerals). Results: Weight gain and daily weight gain were higher for calves in the T-Control, T-500, and T-1000 groups. The concentration of heavy-chain immunoglobulins was higher in the blood of calves in the T-Control and T-500 groups when compared to the other groups. In the T-1500 groups, higher levels of reactive oxygen species were observed, while, in the T-0 and T-1500 groups, higher levels of TBARS and glutathione S-transferase activity were detected. The 15 abundant microorganisms in the calves’ feces, regardless of treatment, were Treponema suis, Treponema saccharophilum, Faecalibacterium prausnitzii, Pseudoflavonifractor sp., Roseburia faecis, Rikenellaceae, Enterobacteriaceae_f, Clostridium sp., Roseburia intestinalis, Aeromonadales_o, Prevotella copri, Treponema succinifaciens, Eubacterium sp., Treponema porcium, and Succinivibrio sp. The T-1000 group showed greater alpha diversity for the intestinal microbiota than T-Control, T-0, and T-500. The additive combination (T-1000) increased the bacterial activity in the ruminal fluid, and the animals of T-1000 had a higher concentration of short-chain fatty acids compared to T-0 and T-1500; this difference is because, in these calves, the production of acetic, butyric, and propionic acid increased. Conclusions: The combination of additives had positive effects on animal health, ruminal volatile fatty acid production, and intestinal microbiota, resulting in animals with more significant weight gain and feed efficiency.